Drama-Based Pedagogy in Vocabulary Learning Through Speaking Skills: A Classroom Action-Based Research - Ketut Filia Budi Agustini; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti (Universitas Pendidikan Ganesha, 2025)
Low vocabulary mastery and lack of confidence in speaking English are major obstacles in the learning process. Students often have difficulty expressing ideas verbally due to limitations in their vocabulary. This study aims to analyze the effectiveness of implementing Drama-Based Pedagogy in improving students' vocabulary mastery through speaking skills by involving students' critical and creative thinking abilities (C4–C6). This study is a collaborative Classroom Action Research (CAR) with a two-cycle design consisting of planning, action, observation, and reflection stages. The research subjects were one class of ninth-grade students. Data were collected through observation, interviews, and oral tests (pre-test, cycle 1, and cycle 2). The instruments used included observation guidelines, interview guidelines, and oral test assessment sheets. The data analysis techniques used were quantitative and qualitative descriptive methods to examine changes in scores and students' and teachers' responses to the learning process. The results of the study showed an increase in the average vocabulary mastery score from 53.2 in the pre-test to 72.2 at the end of cycle 1, and reached 81.3 at the end of cycle 2. Interviews with students and teachers indicated that this approach provided an enjoyable, contextual learning experience and motivated students to actively speak. The conclusion of this study indicates that Drama-Based Pedagogy effectively improves vocabulary mastery while building students' confidence in speaking English. The implications of this study are that teachers may consider this approach as an alternative in interactive English language learning strategies focused on enhancing speaking skills.